The role of green buildings in achieving the sustainable development goals - Abdul Ghani Olabi; Nabila Shehata; Usama Hamed Issa; O.A. Mohamed; Montaser Mahmoud; Mohammad Ali Abdelkareem; M.A. Abdelzaher (International Journal of Thermofluids)
The Sustainable Development Goals (SDGs) are a group of 17 objectives established by the United Nations (UN) and specified in resolutions adopted by the UN general assembly on September 25, 2015, and January 1, 2016. These broad aims, which collectively encompass 169 goals, are interconnected even though they have their own unique objectives. Numerous environmental, social, and economic development challenges are covered under the SDGs. This paper discusses the role of green buildings in achieving the UN's SDGs and investigates the issues related to their design and barriers. It is clearly demonstrated that the reliance on renewable energy resources is one of the key elements of green buildings. Additionally, the integration between these resources is considered a promising approach to achieving net zero energy consumption. This paper also aims to emphasize the positive effects that these green buildings have on people, the environment, and the economy, which ensures their survival. It also discusses several aspects related to green buildings, including materials, site evaluation, and greening existing buildings.